Polyfunctional KLRG-1+CD57+ Senescent CD4+ T Cells Infiltrate Tumors and Are Expanded in Peripheral Blood From Breast Cancer Patients - Ramello, Maria C.; Núñez, Nicolás G.; Tosello Boari, Jimena; Bossio, Sabrina N.; Canale, Fernando P.; Abrate, Carolina; Ponce, Nicolas; Del Castillo, Andrés; Ledesma, Marta; Viel, Sophie; Richer, Wilfrid; Sedlik, Christine; et al. (Frontiers in Immunology, 2021)
Senescent T cells have been described during aging, chronic infections and cancer; however, a comprehensive study of the phenotype, function and transcriptional program of this T cell population in breast cancer (BC) patients is missing. Compared to Healthy Donors (HD), BC patients exhibit an accumulation of KLRG-1+CD57+ CD4+ and CD8+ T cells in peripheral blood. These T cells infiltrate tumors and tumor-draining lymph nodes. KLRG-1+CD57+ CD4+ and CD8+ T cells from BC and HD exhibit features of senescence and, despite their inhibitory receptors expression, they produce more effector cytokines and exhibit higher expression of Perforin, Granzyme B and CD107a than non-senescent subsets. When compared to blood counterparts, tumor-infiltrating senescent CD4+ T cells show similar surface phenotype but reduced cytokine production. Transcriptional profiling of senescent CD4+ T cells from the peripheral blood of BC patients reveals enrichment in genes associated with NK or CD8+-mediated cytotoxicity, TCR-mediated stimulation and cell exhaustion compared to non-senescent T cells. Comparison of the transcriptional profile of senescent CD4+ T cells from peripheral blood of BC patients with those of HD highlighted marked similarities but also relevant differences. Senescent CD4+ T cells from BC patients show enrichment in T-cell signaling, processes involved in DNA replication, p53 pathways, oncogene-induced senescence, among others compared to their counterparts in HD. High gene expression of CD4, KLRG-1, and B3GAT1 (CD57), which correlates with increased overall survival for BC patients, underscores the usefulness of the evaluation of the frequency of senescent CD4+ T cells as a biomarker in the follow-up of patients.